Performance of Starter Broilers Fed Raw Pigeon Pea [Cajanus cajan (L.) Millsp.] Seed Meal Diets Supplemented with Lysine and or Methionine - Amaefule , K.U.; Ukpanah, U.A.; Ibok, A.E. (International Journal of Poultry Science, 2011)
Performance of starter broilers fed raw Pigeon Pea [Cajanus cajan (L.) Millsp.] Seed Meal (PSM) diets supplemented with lysine and or methionine was determined with 270 unsexed broilers. The experimental design was 2 x 4 factorial in a Completely Randomized Design (CRD), with each dietary treatment replicated three times and 10 broilers per replicate. The factors were inclusion level of raw PSM (30 and 40%) and amino acid supplementation (no supplementation, lysine, methionine and lysine + methionine). There was a conventional maize-soybean diet as positive control while raw PSM without supplementation was the negative control. Lysine and methionine supplementation were 0.10 and 0.25%, respectively. Performance criteria measured were weight gain, feed intake, Feed Conversion Ratio (FCR), Protein Efficiency Ratio (PER) and live weight at 4th week. Results showed that broilers fed methionine or lysine + methionine supplemented diets had significantly (p<0.05) higher live weight, live weight gain, feed intake and significantly (p<0.05) lower protein intake than broilers fed diet supplemented with lysine. Amino acid supplementation significantly (p<0.05) affected only live weight and daily weight gain of broilers. The diet of 40% raw PSM significantly (p<0.05) increased cost per kg feed and daily feed cost more than 30% PSM diet. It was concluded that starter broilers could be fed up to 40% raw Pigeon Pea Seed Meal (PSM) diet without adverse effect on performance of starter birds. However, the diet of 30% PSM should be supplemented with methionine and that of 40% with lysine + methionine.